2021
DOI: 10.3389/fcell.2021.755544
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Regeneration of Ganglion Cells for Vision Restoration in Mammalian Retinas

Abstract: Glaucoma and other optic neuropathies affect millions of people worldwide, ultimately causing progressive and irreversible degeneration of retinal ganglion cells (RGCs) and blindness. Previous research into cell replacement therapy of these neurodegenerative diseases has been stalled due to the incapability for grafted RGCs to integrate into the retina and project properly along the long visual pathway. In vivo RGC regeneration would be a promising alternative approach but mammalian retinas lack regenerative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 63 publications
(112 reference statements)
5
40
4
Order By: Relevance
“…During the past decade, many groups have sought to identify key pathways and transcription factors responsible for MG-mediated retinal repair in zebrafish and other species, with the hope of recapitulating the full regenerative processes in mammals. Having built on these findings, several recent high-profile in vivo studies show that after manipulating key regulators in the adult mouse retina, endogenous MG can be reprogrammed to generate multiple types of retinal neurons, including rod photoreceptors ( Yao et al, 2018 ), bipolar or amacrine-like interneurons ( Jorstad et al, 2017 ; Hoang et al, 2020 ), and RGCs ( Zhou et al, 2020 ; Xiao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…During the past decade, many groups have sought to identify key pathways and transcription factors responsible for MG-mediated retinal repair in zebrafish and other species, with the hope of recapitulating the full regenerative processes in mammals. Having built on these findings, several recent high-profile in vivo studies show that after manipulating key regulators in the adult mouse retina, endogenous MG can be reprogrammed to generate multiple types of retinal neurons, including rod photoreceptors ( Yao et al, 2018 ), bipolar or amacrine-like interneurons ( Jorstad et al, 2017 ; Hoang et al, 2020 ), and RGCs ( Zhou et al, 2020 ; Xiao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first study by Zhou et al utilized the CRISPR-CasRx system to knock down the expression of Ptbp1 , resulting in MG-to-RGC conversion in the adult mouse retina ( Zhou et al, 2020 ). The second study by Xiao et al reported highly efficient MG-to-RGC conversion after ectopic expression of Math5 and Brn3b, two transcription factors that promote the RGC fate ( Xiao et al, 2021 ). Strikingly, these two studies also reported that newly generated RGC regrew their axons through long-distance travel within the optic nerve all the way to the target regions in the brain, re-establishing the retina-brain connection.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations